2016
DOI: 10.1128/jvi.02545-15
|View full text |Cite
|
Sign up to set email alerts
|

An Adenovirus DNA Replication Factor, but Not Incoming Genome Complexes, Targets PML Nuclear Bodies

Abstract: Promyelocytic leukemia protein nuclear bodies (PML-NBs) are subnuclear domains implicated in cellular antiviral responses. Despite the antiviral activity, several nuclear replicating DNA viruses use the domains as deposition sites for the incoming viral genomes and/or as sites for viral DNA replication, suggesting that PML-NBs are functionally relevant during early viral infection to establish productive replication. Although PML-NBs and their components have also been implicated in the adenoviral life cycle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 44 publications
0
32
4
Order By: Relevance
“…BrdU (5-bromo-2’-deoxyuridine) is a classical analog widely used for DNA labeling, but requires stringent denaturing for detection using antibodies, similar to FISH. However, when combined with nuclease treatments, incorporated BrdU can be detected with antibodies without denaturing, and this method has been used to visualize viral genomes such as Ad DNAs [26]. …”
Section: Experimental Strategies To Study Nuclear Antiviral Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…BrdU (5-bromo-2’-deoxyuridine) is a classical analog widely used for DNA labeling, but requires stringent denaturing for detection using antibodies, similar to FISH. However, when combined with nuclease treatments, incorporated BrdU can be detected with antibodies without denaturing, and this method has been used to visualize viral genomes such as Ad DNAs [26]. …”
Section: Experimental Strategies To Study Nuclear Antiviral Factorsmentioning
confidence: 99%
“…Based on this property, we recently developed a live-cell imaging technique, showing that EGFP-tagged TAF-I forms infection-specific nuclear puncta reflecting Ad genome localization in living cells [72]. Using these imaging tools, we have reported that incoming Ad genomes neither target nor are targeted by PML-NBs immediately after infection [26]. Furthermore, absence of co-localization between incoming Ad genomes and PML-NBs is neither cell type-specific nor reversed by IFN treatments, as has been shown by our and recent independent studies [26,27,73].…”
Section: Adenovirusmentioning
confidence: 99%
See 3 more Smart Citations